EFEKTIVITAS SISTEM DAN PROSEDUR PENGELOLAAN BARANG MILIK DAERAH SESUAI PERMENDAGRI NO. 17 TAHUN 2007 PADA PEMERINTAH DAERAH KABUPATEN KONAWE - Safaruddin, Safaruddin; Dali, Nasrullah; Firman, La Ode (JURNAL AKUNTANSI DAN KEUANGAN, 2018)
ABSTRACK This study aims to determine the effectiveness of the implementation of systems and procedures for the management of local property in accordance with Permendagri No. 17 of 2007 on the technical implementation of the management of local property on the Regional Government of Konawe Regency. Sample in this research is officer or staff directly involved in the process of management of local property that is Head of SKPD as user of goods amounting to 15 people at 15 SKPD representing Office, Agency and District. The analytical method used is descriptive statistical analysis. The result of the research shows that the implementation of system and procedure of management of local property at Local Government of Konawe Regency not yet effective. The problems encountered are the implementation of storage procedures of goods where the absence of warehouse where the goods belonging to the area in each SKPD so that the administration does not store inventory goods, the procedure of administration of local property has not been in accordance with the prevailing rules of the inventory of local property has not presented data and information sufficient, there are still many goods belonging to the regions that do not have ownership documents so that it is necessary to optimize the security procedures of goods and the implementation of the compensation claims that have not been fully implemented as applicable rules Keywords: Effectiveness, System, Procedures, Management of Regional Property, Permendagri No. 17 of 2007